CD10 stromal expression in phyllodes tumours - Nur Syahrina Rahim; Siti-Aishah MA; Nurhayati HM; Reena RMZ; Rohaizak M; Norlia A (Universiti Kebangsaan Malaysia, 2024)
7th Malaysia Indonesia Brunei Medical Science Conference 'TOWARDS A HOLISTIC AND INTEGRATIVE APPROACH IN HEALTHCARE'